MENINGKATKAN KEMAMPUAN GENERALISASI MATEMATIK DAN KEPERCAYAAN DIRI SISWA SMP DENGAN PENDEKATAN METAPHORICAL THINKING - Lesmana, Leni Andriana; Hidayat, Wahyu; Rohaeti, Euis Eti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to determine the increased ability of mathematical generalization and self-confidence of students junior hight school with Methaporical Thinking approach. The research method used is an experimental method involving 2 classes, namely experimental class and control class. The sample of this study was chosen randomly with the number of samples were 30 students of class XII at SMP RAHAYU. And elected class 7-1 as experimental class and class 7-2 as control class. In each data collection each student will be given the same pretest and postes. Intrument used is a test of mathematical generalization ability and scale of confidence. From the calculation and hypothesis test, it can be concluded that the improvement of mathematical generalization ability of the experimental class is significantly better than the control class, then most of the students who get the learning with methaporical thinking had better self confidence than ordinary learning.